Pelaksanaan Kredit Usaha Rakyat Pada Bank Syariah Mandiri Di Kabupaten Pati - Muhamad Nadratuzzaman Hosen; Mas Arif (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
One of Government Programs in encouraging for small and medium enterprises (SMEs) is Kredit Usaha Rakyat (KUR). The purpose of the implementation of the program to address the capital investment problem particularly un-bankable proposal. KUR makes SMEs will be able to obtain financing. Then the government authorize the commercial bank for the implementation. One of the authorized commercial bank is Bank SyariahMandiri (BSM). This paper present the findings that debtors characteristics of KUR in BSM is 57.69% male, 85.71% of enterprises, 50% of high school graduates, and 50% of debtors have been become SMEs between 1-10 years. The determinant factors of the debtors of KUR in BSM assumed into five variables, namely information KUR procedures, debtor perception of the KUR, transaction costs, their understanding the value of KUR and Islamic values.